Systems Analysis Tools for Better Health Care Delivery - Pardalos, Panos M.; Georgiev, Pando G.; Papajorgji, Petraq; Neugaard, Britta; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This book presents some recent systems engineering and mathematical tools for health care along with their real-world applications by health care practitioners and engineers. Advanced approaches, tools, and algorithms used in operating room scheduling and patient flow are covered. State-of-the-art results from applications of data mining, business process modeling, and simulation in healthcare, together with optimization methods, form the core of the volume. Systems Analysis Tools for Better Health Care Delivery illustrates the increased need of partnership between engineers and health care professionals. This book will benefit researchers and practitioners in health care delivery institutions, staff members and professionals of specialized hospital units, and lecturers and graduate students in engineering, applied mathematics, business administration and health care.
Keywords: Mathematics; Practice of medicine; Mathematical optimization; Mathematics; Optimization; Operations Research, Management Science; Health Administration; Mathematical Modeling and Industrial Mathematics